The Urgency of Knowledge Transformation with Multi-, Inter-, and Transdisciplinary Approaches in the Complexities of Humanity's Problems - Suud Sarim Karimullah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2022)
This study tries to transform knowledge to answer various problems amid the complexity of human problems by taking a multi-inter-transdisciplinary scientific approach. At the same time, library research is used in this study with data sources taken from literature searches with a qualitative approach through analysis with a descriptive-analytic pattern. Then, this study states that the transformation of knowledge with a multi-, inter-, and transdisciplinary scientific approach is a pattern of academic interaction that illustrates that the complexity of human problems cannot be responded to by using monodisciplinary alone because each scientific discipline cannot stand alone. Scientific dialogue across disciplines is necessary because every scientific discipline is interrelated and complementary. A multi-, inter-, and transdisciplinary scientific approach will be able to become a solution to the complexity of the problems that occur if policymakers (executive-legislative institutions), academic institutions (universities), and various community leaders sit together to solve various complex problems in community life.